Racial and Ethnic Disparities in Perinatal Insurance Coverage. Issue 4 (April 2020) - Daw, Jamie R.; Kolenic, Giselle E.; Dalton, Vanessa K.; Zivin, Kara; Winkelman, Tyler; Kozhimannil, Katy B.; Admon, Lindsay K.
Abstract : OBJECTIVE: To measure the association between race–ethnicity and insurance status at preconception, delivery, and postpartum and the frequency of insurance gaps and transitions (disruptions) across these time points. METHODS: We conducted a cross-sectional analysis of survey data from 107, 921 women in 40 states participating in the Centers for Disease Control and Prevention's Pregnancy Risk Assessment and Monitoring System from 2015 to 2017. We calculated unadjusted estimates of insurance status at preconception, delivery, and postpartum and continuity across these time points for seven racial–ethnic categories (white non-Hispanic, black non-Hispanic, indigenous, Asian or Pacific Islander, Hispanic Spanish-speaking, Hispanic English-speaking, and mixed race or other). We also examined unadjusted estimates of uninsurance at each perinatal time period by state of residence. We calculated adjusted differences in the predicted probability of uninsurance at preconception, delivery, and postpartum using logistic regression models with interaction terms for race–ethnicity and income. RESULTS: For each perinatal time point, all categories of racial–ethnic minority women experienced higher rates of uninsurance than white non-Hispanic women. From preconception to postpartum, 75.3% (95% CI 74.7–75.8) of white non-Hispanic women had continuous insurance compared with 55.4% of black non-Hispanic women (95% CI 54.2–56.6), 49.9% of indigenous women (95% CI 46.8–53.0) and 20.5% of Hispanic Spanish-speaking women (95% CI 18.9–22.2). In adjusted models, lower-income Hispanic women and indigenous women had a significantly higher predicted probability of uninsurance in the preconception and postpartum period compared with white non-Hispanic women. CONCLUSION: Disruptions in perinatal insurance coverage disproportionately affect indigenous, Hispanic, and black non-Hispanic women. Differential insurance coverage may have important implications for racial–ethnic disparities in access to perinatal care and maternal–infant health. Abstract : Gaps and transitions (disruptions) in perinatal insurance coverage disproportionately affect indigenous, Hispanic, and black non-Hispanic women.